TiO2 Nanoparticle Filler-Based Mixed-Matrix PES/CA Nanofiltration Membranes for Enhanced Desalination - Mehwish Batool; Amir Shafeeq; Bilal Haider; Nasir M. Ahmad (Membranes, 2021)
Mixed-matrix nanocomposite (PES/CA/PVP) membranes were fabricated for water desalination by incorporating varying amount of titanium dioxide nanoparticles (TiO2 NPs) ranging from 0 and 2 wt. %. Efficient dispersion of nanoparticles within polymeric membranes was achieved using the chemical precipitation method for uniform surface generation, and an asymmetric morphology was achieved via phase inversion method. Finally, membranes were characterized by Fourier Transform Infrared (FTIR) spectroscopy, Thermo Gravimetric Analysis (TGA), Scanning Electron Microscopy (SEM), porosity and contact angle analysis. FTIR confirmed chemical composition of membranes in terms of polymers (PES/CA/PVP) and TiO2. TGA analysis confirmed an increase in thermal stability of membranes with the increase of TiO2 nanoparticles loading. The addition of TiO2 nanoparticles also resulted in an increase in porous structures due to an increase in mean pore size, as shown by SEM results. An increase in the hydrophilicity of the membranes was observed by increasing the concentration of TiO2 nanoparticles. The present study investigated pristine and mixed-matrix nanocomposite NF membrane performance while filtering a NaCl salt solution at varying concentration range (from 1 to 4 g/Lit 6 bar). The prepared membranes demonstrated significant improvement in water permeability and hydrophilicity. Further, to optimize the water flux and salt rejection, the concentration of Polyvinylpyrrolidone (PVP) was optimized along with TiO2 nanoparticles. Both the water flux and salt rejection of the fabricated membranes were observed to increase with an increase inTiO2 nanoparticles to 2 wt. % loading with optimized PVP concentration, which demonstrated the improved desalination performance of resultant membranes.